2011
DOI: 10.1080/10920277.2011.10597629
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Measurement at Advanced Ages

Abstract: Accurate estimates of mortality at advanced ages are essential to improving forecasts of mortality and the population size of the oldest old age group. However, estimation of hazard rates at extremely old ages poses serious challenges to researchers: (1) The observed mortality deceleration may be at least partially an artifact of mixing different birth cohorts with different mortality (heterogeneity effect); (2) standard assumptions of hazard rate estimates may be invalid when risk of death is extremely high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 44 publications
6
67
0
Order By: Relevance
“…This differential survival leads to excess of fall-born persons among centenarians [40]. These findings support the idea of early-life programming of human aging and longevity, and are in a good agreement with our earlier reports on the effects of month-of-birth on mortality in the United States [41], and are consistent with our study of centenarians and shorter-lived peers (see above). The results of our study were obtained by using a more conclusive within-family analysis, and were not confounded by between-family variation.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…This differential survival leads to excess of fall-born persons among centenarians [40]. These findings support the idea of early-life programming of human aging and longevity, and are in a good agreement with our earlier reports on the effects of month-of-birth on mortality in the United States [41], and are consistent with our study of centenarians and shorter-lived peers (see above). The results of our study were obtained by using a more conclusive within-family analysis, and were not confounded by between-family variation.…”
Section: Introductionsupporting
confidence: 93%
“…First, mortality deceleration may be caused by age misreporting in death data for older individuals [18, 19]. Studies conducted more than 10 years ago used data for older birth cohorts when age reporting was not particularly accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than making the strong assumption of a linear decline in vitality, and also for the purpose of focusing on the aging process in old age, I confine the analysis to the decline in vitality after age 70. 2 Because of problems of death underregistration and age uncertainty at very old ages, even in the best historical data (Crimmins and Finch 2006; Gavrilov and Gavrilova 2011), I restrict the upper end of age in my analysis to 94.…”
Section: Methodsmentioning
confidence: 99%
“…This contributes to the deceleration of mortality at late ages: the rate at which the mortality hazard changes with age levels off after age 110 (Thatcher et al 1998; Vaupel 2010b; Vaupel et al 1998). The deceleration of mortality in very late life might be due to the underregistration of deaths or age uncertainty among very old adults, and these problems might plague even the best historical data (Crimmins and Finch 2006; Gavrilov and Gavrilova 2011). Keeping this possible limitation in mind, I aim to study how population heterogeneity may shape cohort patterns in mortality acceleration before very late ages (e.g., age 95).…”
Section: Population Heterogeneity Mortality Selection and The Strehmentioning
confidence: 99%
“…Because the law is considered to be a good approximation of the mortality pattern that occurs between sexual maturity and old age, recent research has paid more attention to what happens beyond rather than within the predictable age interval of the law. Researchers have generally observed that a leveling off of the mortality rate at very old ages (later than age 85)—the so-called old-age plateau—would directly follow the exponential increase (Carey and Liedo 1995; Horiuchi and Wilmoth 1998; Vaupel et al 1998), although controversy remains regarding the age to which the Gompertz law can be extended (Gavrilov and Gavrilova 2011). However, a relatively subtle but systematic deviation from the law between late-middle and early-old ages (50–70) was identified in a few studies, which found that the rate of mortality increase became either faster or slower than the predicted exponentially increasing trajectory (Ekonomov et al 1989; Himes et al 1994; Horiuchi 1983, 1997; Horiuchi and Coale 1990; Horiuchi and Wilmoth 1998; Milne 2007; Pakin and Hrisanov 1984).…”
Section: Introductionmentioning
confidence: 99%